Comparison of Physical Properties and Strength of Geopolymer Mortar with White Soil Substitution and Mortar with Portland Pozzolan Cement under Corrosive Seawater Conditions - Yulita Arni Priastiwi; Rudi Yuniarto Adi; Arif Hidayat; Abi Nabil Hanif; Bima Bima (Universitas Diponegoro, 2023)
Construction also causes environmental pollution due to excessive cement production, so an alternative to cement is needed. Geopolymer is considered an alternative material to replace cement. This research compares three variations of mortar (PPC, geopolymer, and geopolymer with white soil) in a seawater environment. Research in the laboratory with 5x5x5 cm mortar specimens and test parameters for porosity, compressive and direct tensile strength, density, and absorption has been carried out. Microstructure due to immersion effect was also carried out but only on MGT15 mortar. The results showed that the PPC mortar had the highest compressive and tensile strength among the three variations, namely 27.80 MPa and 2.540 MPa at 28 days of age, the most negligible porosity and absorption were 1.124% and 76 gram/100cm2, and increased density after immersion. However, when immersing for 56 days, the decrease in strength reached 21%, while geopolymer mortar tended to be stable and even increased to 19%. Microstructure tests in the form of SEM and EDX on MGT15 showed the effect of seawater immersion, such as the presence of cracks, ettringite, and bad reactions. Soaking in seawater caused a decrease in some mortar strength supporting compounds and the appearance of 0.3% free chloride at 28 days of immersion.